2009
DOI: 10.1053/j.ajkd.2009.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Major Depressive Episode in CKD

Abstract: Background Depression is prevalent in long-term dialysis patients and is associated with death and hospitalization. Whether depression is present through all chronic kidney disease (CKD) stages or appears after dialysis therapy initiation is not clear. We determined the prevalence of a major depressive episode and other psychiatric illnesses by using a structured gold-standard clinical interview and demographic and clinical variables associated with major depressive episode in patients with CKD. Study Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
154
5
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 43 publications
12
154
5
7
Order By: Relevance
“…In our study, as a result of interviews with SCID-I, any psychiatric disorder was diagnosed in 49% of patients, and major depressive disorder was diagnosed in 28.6%, and these rates were significantly higher than control group. Results of our study are consistent with the results of other studies pointing out to the frequent existence of comorbid psychiatric disorders in patients with chronic renal impairment (19,20,33,35). Parallel to this finding, the depression subscale score of HADS is significantly higher in patient group than in the control group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, as a result of interviews with SCID-I, any psychiatric disorder was diagnosed in 49% of patients, and major depressive disorder was diagnosed in 28.6%, and these rates were significantly higher than control group. Results of our study are consistent with the results of other studies pointing out to the frequent existence of comorbid psychiatric disorders in patients with chronic renal impairment (19,20,33,35). Parallel to this finding, the depression subscale score of HADS is significantly higher in patient group than in the control group.…”
Section: Discussionsupporting
confidence: 93%
“…A review of studies using different scales and strategies for diagnosis shows that the frequency of comorbid psychiatric disorders in ESRD ranges from 5% to 50% (19,32,33). In a study, it was reported that according to Beck Depression Inventory, 47% of the patients with ESRD have a score above the cutoff point, but major depression is diagnosed in only 5% of them as a result of structured interviews (32).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that 22.7% of patients with early stages of CKD had a current MDE, which is consistent with previous studies [1,15]. Our results also demonstrated that diabetes mellitus were significantly associated with an MDE.…”
Section: Discussionsupporting
confidence: 93%
“…Depression is prevalent in patients with chronic kidney disease (CKD), affecting up to 21% of patients even before receiving maintenance dialysis [1]. The presence of depression is associated with increased risk of progression to dialysis, reduced quality of life, hospitalization, and death [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Half of the patients who start dialysis in the United States are aged .65 years and the majority have multiple chronic conditions in addition to ESRD. Although dialysis therapy extends life for most patients with ESRD, it often fails to restore health, and despite frequent contact with the healthcare system, many patients suffer from unrecognized and untreated distressing symptoms, functional and cognitive disability, and high caregiver burden before death (2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%